2007
DOI: 10.1016/j.rse.2007.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Using remotely-sensed estimates of soil moisture to infer soil texture and hydraulic properties across a semi-arid watershed

Abstract: Near-surface soil moisture is a critical component of land surface energy and water balance studies encompassing a wide range of disciplines. However, the processes of infiltration, runoff, and evapotranspiration in the vadose zone of the soil are not easy to quantify or predict because of the difficulty in accurately representing soil texture and hydraulic properties in land surface models. This study approaches the problem of parameterizing soils from a unique perspective based on components originally devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
93
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 60 publications
7
93
0
Order By: Relevance
“…It has been demonstrated that batch calibration using soil moisture can result in a better match between modelled and observed soil moisture [139]. However, these studies focused on improved surface or root-zone soil moisture simulation through either conceptual models or physically-based models [138,[140][141][142][143]. From the flood forecasting perspective, a more important question is how the batch calibration using soil moisture affects the streamflow simulation/forecasting.…”
Section: Batch Calibrationmentioning
confidence: 99%
“…It has been demonstrated that batch calibration using soil moisture can result in a better match between modelled and observed soil moisture [139]. However, these studies focused on improved surface or root-zone soil moisture simulation through either conceptual models or physically-based models [138,[140][141][142][143]. From the flood forecasting perspective, a more important question is how the batch calibration using soil moisture affects the streamflow simulation/forecasting.…”
Section: Batch Calibrationmentioning
confidence: 99%
“…In fact, Santanello et al (2007) 795 modified the FXEXP parameter in their study to be 1.0, due to the semi-arid region and inability coverage (e.g. Mitchell et al 2004, LeMone et al 2010, Trier et al 2011.…”
mentioning
confidence: 99%
“…for mixed crops or soil 191 types). This can be a problem, particularly for soils where larger differences in soil parameters 192 have been observed within a soil type than between types (Feddes et al 1993;Soet and Stricker 193 2003; Gutmann and Small 2005;Santanello et al 2007). …”
mentioning
confidence: 99%
See 2 more Smart Citations